Pengaruh Dosis Pupuk Ponska terhadap Pertumbuhan dan Hasil Tanaman Kangkung Darat (Ipomoea Reptans Poir) - Marsinah Marsinah (Jurnal Sains dan Ilmu Terapan, 2025)
Ipomoea reptans (kangkung) is a vegetable that serves as a source of vitamin A, minerals, and other essential nutrients beneficial to human health. One method to increase the yield of Ipomoea reptans is through fertilization. This study aimed to evaluate the effect of different Ponska fertilizer doses on the growth and yield of Ipomoea reptans. The research employed a Randomized Complete Block Design (RCBD) with a single factor, namely the dose of Ponska fertilizer. The treatments consisted of five fertilizer levels, D0 = 0 g/plant or 0 kg/ha, D1 = 10 g/plant or 416 kg/ha, D2 = 20 g/plant or 834 kg/ha, D3 = 30 g/plant or 1,250 kg/ha, and D4 = 40 g/plant or 1,666 kg/ha. Observed variables included plant height, number of leaves, stem diameter, root weight, fresh weight, and dry weight of the plant.